Effects of substituting ytterbium for scandium on the microstructure and age-hardening behaviour of Al–Sc alloy - Tuan, N. Q. (2014)
In order to reduce the cost of Al–Sc alloys and maintain their mechanical properties, the microstructure and mechanical properties of Al–0.24 wt% Sc–0.07 wt% Yb in comparison with Al–0.28 wt% Sc alloys were studied. The aging behaviour, precipitate morphologies, precipitate coarsening and precipitation hardening of both alloys were investigated. The average diameter and the size distribution of nanoscale Al3Sc and Al3(Sc,Yb) precipitates at various aging conditions were measured. Transmission electron microscopy (TEM) and high-resolution TEM were used to deeply understand the precipitate evolution. A maximum hardness around 73 (HV30) was obtained with a precipitate diameter from 4.3 to 5.6 nm for both alloys.